Ergonomic Oriented Working for Controlling Photokeratitis and MSD Complaints in the Informal Welding Sector - Suherdin, Suherdin; Lolan, Yosef Pandai; Rasyadi, Fikran Hafizh (Universitas Airlangga, 2024)
Introduction:Informal welding workers often experience health problems such as musculoskeletal disorders (MSDs) and photokeratitis. Hazard identification revealed that informal welding sector workers in Bogor Street, Bandung City have a high risk of MSDs (75%) and photokeratitis (51.7%). This study aims to analyze the differences between MSD and photokeratitis complaints based on the results of ergonomic oriented working intervention. Methods: This study used an experimental design with a quantitative approach. Two treatments were administered to participants and the results of the ergonomic oriented working intervention were measured twice. The population of this study consisted of informal welding workers who met the inclusion and exclusion criteria. The minimum sample size required was calculated to be 33 workers using the comparison of two means formula. Data were collected using a simple random sampling technique and analyzed using a paired t-test and the Wilcoxon signed-rank test. Results: The analysis revealed that the mean scores for photokeratitis and MSD complaints were lower with ergonomic oriented working than with non-ergonomic oriented working. There was a significant difference in the incidence of photokeratitis complaints (p = 0.005) and MSD complaints (p < 0.001) before and after working with and without ergonomic oriented intervention. Conclusion: Ergonomic oriented working has been found to effectively control photokeratitis and MSD complaints.